Perancangan Sistem Informasi Manajemen Elektronik Arsip (E-Arsip) dalam Lingkup Perkantoran - Achaliyah, Siti; Muhtar, Octa Dewangga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2023)
These modern companies and offices are experiencing quite rapid growth. These conditions have an impact on increasing the number of document archives supporting the company's performance. To support optimization and minimize the risk of loss of archives, it is necessary to develop an optimal filing system. This is the background for the author to design an Electronic Archive (EArchive) application for Archive Management in a company that is integrated with a Management Information System. The use of integrated E-Archives has the advantage of accelerating the search process for archives so that the service needs of the community, employees, and parties interested in company data can be served easily. To produce an archive digitization system for companies, information system design is carried out using software such as MySQL, PHP, XAMPP, Sublime Text 3, Ms. Office Visio 2019, and Google Chrome as a browser application. The menu features presented in the E-Archive include login, Dashboard, Company Profile, Users, Master Data, Archive Management, Reports, and Log Out. By using this system, filing management at companies can be more effective and efficient in searching and retrieving archived documents.